Impact of FAAH Genotype and Marijuana Use on Brain Structure and Neuropsychological Performance in Emerging Adults - (:unkn) unknown (My University, 2014)
Introduction: Chronic MJ use may be associated with higher cognitive ability impairments (see Lisdahl et al., 2013). Regions undergoing later maturation (Gogtay 2004), may be at increased risk for MJ-induced alterations. Endogenous cannabinoid signaling (ECS) is modulated by the function the enzyme Fatty Acid Amide Hydrolase (see Ho & Hilard, 2005), thus the gene encoding for this enzyme (FAAH) impacts ECS (Sipe et al., 2002). Here, we examine the impact of MJ use and FAAH genotype on PFC complexity and underlying frontal white matter (WM) integrity in young adults. Methods: Participants included 37 MJ users and 37 non-using young adults (ages 18-25). Of those, 27 were FAAH A carriers and 47 were homozygous (C/C) carriers. Exclusion criteria included co-morbid psychiatric and neurologic disorders and excessive other drug use. Brain complexity and WM integrity was measured using local gyrification index and Tracula programs. The Letter Number Sequencing, PASAT and D-Kefs c/w interference measured complex attention and inhibition. Multiple regressions and Pearson r correlations were used to predict LGI, WM integrity and cognitive performance indices from MJ use status, FAAH status, and MJ*FAAH interactions controlling for demographic variables and comorbid drug use. Results: MJ users demonstrated decreased LGI in bilateral vmPFC (RH: [beta=-.54, p
Keywords: Adolescence; Brain; DTI; Genetics; Gyrification; Marijuana